RESEARCH ON THE DEVELOPMENT OF IRRIGATION PROCEDURES FOR SOYA CULTIVARS ON DESIRABLE SOILS PROTECTED FROM DEFLATION BY BACKHOE BARRIERS - Rakhimov Jora Suyunovich; Sarimsakov Maksudkhon Musinovich; Suyunova O'g'iloy Jo'ra kizi (Journal Park Publishing, 2025)
Research was conducted to study the irrigation regimes of soybean varieties in areas protected from wind erosion by cover barriers in 2021-2023 on deflated barren soils of the "At the Level of Opportunity" farm in the Koson district of the Kashkadarya region.
Keywords: Deflation, granulometric, soil, erosion, clay particles, till layer, genetic layer, middle loam, shade, backfill.